Module 18: Assessment, monitoring and evaluation - Kanamaru, Hideki; Hancock, J.; Bockel, Louis; Braimoh, A.K.; Förch, Wiebke; Grewer, Uwe; Hiepe C; Jonsson M; Krishnamurthy K; Marais S; Medeiros K; Matteoli F; et al. (Food and Agriculture Organization of the United Nations, 2013)
This module looks at assessment, monitoring and evaluation frameworks that are necessary for the successful adoption of climate-smart agriculture (CSA). Focus is placed mainly at the subnational and national levels. However, some case studies address activities at the farm or project level. The module presents an overview of important climate change-related assessment, monitoring and evaluation activities in policy and programme processes and project cycles. The purposes of these activities, baselines, and associated concepts are also described. Details are provided about how to conduct assessments relating to policies and project justification and design, as well as monitoring and evaluation. In the last section, the specific challenges to assessment, monitoring and evaluation in the context of CSA are reviewed and some guiding principles for addressing them are offered.